Forms of Capital in F. Scott Fitzgerald’s “Winter Dreams” - Akhavi Zadegan, Raheleh; Pirnajmuddin, Hossein (Miscelánea: A Journal of English and American Studies, 2019)
This paper offers a reading of F. Scott Fitzgerald’s “Winter Dreams” (1922) in the light of Pierre Bourdieu’s theorization of forms of capital. Fitzgerald’s story is centrally concerned with social class and addresses the rise of consumer culture in the 1920s. It is about a Midwest American trying to improve his economic and social status to win the hand of a wealthy girl he loves. At issue here are different types of capital (economic, social, cultural, symbolic), hence the relevance of Bourdieu. Thus, we explore in Fitzgerald’s story the way characters are engaged in everyday practices as social agents competing with other social agents to accumulate ‘capital’. In the process of socialization, the economic capital provides the protagonist with luxury but the lack or shortage of other forms of capital —especially cultural capital— cause him to fail in the pursuit of his heart’s desire.